Ulysses of Embra - Johnston Paul (American, British and Canadian Studies Journal, 2017)
A critical day in the life of Leonard Rose, an Edinburgh (Embra) criminal with undertones of Homer’s Odysseus and James Joyce’s Leopold Bloom. He thinks of his son, Stevie, whom he has not seen for fifteen years. After his morning ablutions he attends the cremation service of a notable lawyer, who had ties to local crime kingpin, Big Sam. Leonard is shaken by visions of the people he murdered for Big Sam. Stevie is waiting outside, accompanied by two detectives. Leonard is told that his ex-wife, Penny, is setting up Glasgow gang boss Boy ‘The Boiler’ Boyle. Leonard takes the police to his bar, the End of the World, aware that Big Sam’s number two, Nessie, is following. After knocking the policemen out and overpowering Nessie and his men, Leonard and Stevie go to Big Sam’s palatial home. When he understands that Penny intended to betray Big Sam as well, Leonard deserts his son and goes home, free of emotional and professional ties. He decides to leave Edinburgh and go inland, where no one knows him. But before that he will knock on his female neighbour’s door, hoping she will give his attentions a positive reception.